Evaluation of Antioxidant, Toxicity, and Antidiabetic Activities of Young Sprouts of Hordeum vulgare, Triticum aestivum, and Zea mays - Kalauni, Surya Kant; Bhattarai, Gita; Khanal, Lekha Nath (Journal of Institute of Science and Technology, 2024)
The germination of dormant seeds triggers various metabolic reactions, resulting in the production of essential phytochemicals with diverse biological activities. This contributes to the inclination to consume sprout juices among individuals seeking to enhance their immune system, manage oxidative stress, and prevent complaints associated with metabolic disorders. In this study, we evaluated the antioxidant, toxicity, and antidiabetic activity of young sprout extracts of Hordium vulgare, Triticum aestivum, and Zea mays by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, brine shrimp lethality assay, and α-amylase inhibition methods, respectively. The ethanolic extracts showed the presence of alkaloids, flavonoids, tannins, and polyphenols. The extracts showed moderate antioxidant activity, with Z. mays having the highest capacity, followed by T. aestivum and H. vulgare. Their half-maximal concentration (IC50) values were 54.24±3.35, 95.94±3.29, and 129.26±5.97 μg/mL, respectively. The same trend of toxicity against brine shrimp nauplii was obtained with half-maximal lethal concentration (LC50) values of 326.41, 473.61, and 6768.75 mg/mL respectively. The antioxidant activity across various extracts displayed a positive correlation with the total phenolic and total flavonoid contents. The extracts demonstrated moderate activity in the α-amylase inhibition assay conducted through the starch-iodine method. The outcomes of this study underscore the presence of significant phytochemicals in the young sprouts of commonly consumed cereals, suggesting their potential use as immune boosters and in treating diseases associated with free radicals.